Escherichia coli as a Multifaceted Pathogenic and Versatile Bacterium - Braz, Vânia Santos; Melchior, Karine; Moreira, Cristiano Gallina (Frontiers in Cellular and Infection Microbiology, 2020)
Genetic plasticity promotes evolution and a vast diversity in Escherichia coli varying from avirulent to highly pathogenic strains, including the emergence of virulent hybrid microorganism. This ability also contributes to the emergence of antimicrobial resistance. These hybrid pathogenic E. coli (HyPEC) are emergent threats, such as O104:H4 from the European outbreak in 2011, aggregative adherent bacteria with the potent Shiga-toxin. Here, we briefly revisited the details of these E. coli classic and hybrid pathogens, the increase in antimicrobial resistance in the context of a genetically empowered multifaceted and versatile bug and the growing need to advance alternative therapies to fight these infections.